The influence of diet and exercise on muscle and plasma glutamine concentrations - Blanchard, M. A.; Jordan, G.; Desbrow, B.; MacKinnon, L. T.; Jenkins, D. G. (Medicine & Science in Sports & Exercise, 2001)
Summary The purpose of this study was to determine whether or not carbohydrate intake has an effect on glutamine following high-intensity exercise performed 3 days in a row. It has been suggested that a reduction in glutamine contributes to immune system impairment following prolonged intensive exercise. Five endurance athletes cycled to exhaustion on 3 consecutive days while eating a diet that was either 45% carbohydrate or 70% carbohydrate. Results Glutamine levels were maintained at higher levels for the 70%-carbohydrate group than for the 40%-carbohydrate group. In addition, muscle glycogen concentration was significantly related to glutamine concentration. Implications Cells of the immune system use glutamine in circulation as an energy source, but most cases of infection seem to be an indirect result of too little CHO when the demand (i.e. training) is high. So when¡ CHO intake doesn't meet the demands of training, cortisol rises. Cortisol then decreases the amount of glutamine in circulation by encouraging its uptake by tissues and organs. Since it's the glutamine in circulation that cells of the immune system use, Insufficient CHO as an energy source could set up a chain of events that might affect the health of your athlete Therefore, supplementing with glutamine may elevate total glutamine, but won't necessarily increase levels of circulating glutamine if CHO intake is insufficient. Supplementing with CHO can reduce the cortisol spike, preventing glutamine uptake by tissues and organs and leaving glutamine in circulation to be used by immune system cells.